Clinical Study and Assessment of Efficacy of Polyherbal Combination (KNDBHU) in COVID 19 Patients - Kamal Nayan Dwivedi; Poonam Sharma; Daneshwari Kanashetti; Meghna .; Lalit Nagar (Journal of Pharmaceutical Research)
Even three years after the COVID-19 pandemic initially appeared in December of the year 2019, it is still raging over the globe. There have been numerous attempts to use well-known medications in new ways to treat COVID-19 infection. Many nations, including India, implemented a series of lock downs in an effort to limit the pandemic. Sanitation practices, social seclusion, routine mask wearing, testing, and quarantining of suspected carriers were among the recommended methods for limiting the illness. Numerous treatment strategies have also been used to prevent and treat the illness, but no formal studies using well-known Ayurvedic formulations or any polyherbal combinations have been conducted. A clinical study was planned to test the noble polyherbal combination containing Withania somnifera, Tinospora cordifolia, Moringa oleifera, Adhatoda vasica, Piper longum, Glycyrrhiza glabra, Ocimum sanctum and Curcuma longa. The study checked the rate of symptom remission in individuals receiving the polyherbal combination in addition to standard of care (SoC) to that in patients with mild and moderate symptoms of COVID-19 infections receiving SoC alone. A prospective randomized interventional clinical study was planned comparing outcomes in 2 cohorts with mild to moderate COVID-19 as under. Cohort-1 was trialled with conventional treatment as per government advisory. Cohort-2 was trialled with polyherbal combination and with conventional treatment as per government advisory. With the current add-on Polyherbal regimen, an early clinical improvement in breathlessness was seen along with early ageusia and cough reduction when compared with conventional treatment. The polyherbal combination (KNDBHU) enhanced recovery in COVID-19 Patients. Given the lack of hospital beds in India, the median length of hospital stays was shortened; this development is significant. Keywords: Covid19, Add on polyherbal combinationregimen for Corona virus, Early Clinical Improvement, Shortened hospital stays